Elevated serum creatinine levels and risk of cognitive impairment in older adults with diabetes: a NHANES study from 2011-2014 - Xiao, Yanhua; Devakumar, Veda; Xu, Liyan; Liu, Lei; Mo, Hanyou; Hong, Xuezhi (Frontiers in Endocrinology, 2023)
Background: The brain and kidney have similar microvascular structure, which makes them susceptible to certain common pathophysiological processes. In this study, we examined several indicators of kidney injury/function associated with cognitive function in older diabetic patients in the hope of finding effective markers for detecting cognitive impairment (CI). Methods: A total of 2209 older participants (aged ≥60 years) from the 2011-2014 National Health and Nutrition Examination Survey (NHANES) were analyzed for the association between diabetes and CI using a multiple linear regression analysis model. Using the same approach, we also analyzed the relationship between indicators of kidney injury/function and cognitive function (Animal Fluency Test, Digit Symbol Substitution Test) in the diabetic population. Results: Diabetes was associated with CI. In age-adjusted model, older diabetics performed significantly poorer on tests of cognitive function compared to normoglycaemic individuals (1.145 points lower on the Animal Fluency Test (P = 0.005) and 7.868 points reduced on the Digit Symbol Substitution Test (P < 0.001)). In diabetics, we found elevated serum creatinine (SCr) (especially at SCr≥300uM) was associated with lower scores on cognitive function tests after strict adjustment for potential influences on cognitive function. While albumin/creatinine ratio (ACR) was only associated with Digit Symbol Substitution score (DSS) not Animal Fluency score (AFS), and estimated glomerular filtration rate (eGFR) was only associated with CI (AFS and DSS) at the end-stage renal disease. Conclusion: SCr, as a sensitive indicator of kidney injury, was significantly associated with CI and can potentially be used as an effective marker for screening CI in older diabetics.